A new prediction methodology for dynamic contact pressure distributions in a disc brake - Abu Bakar, Abd. Rahim; Abdul Hamid, Mohd Kameil; Ouyang, Huajiang (Penerbit UTM Press, 2006)
The dynamic contact pressure distribution in a disc brake system remains impossible to measure through experimental methods. This makes numerical analysis using the finite element method an indispensable alternative tool to its prediction. However, the finite element model must first be validated through appropriate analyses so that realistic predicted results can be obtained. This paper proposes and carries out a three-stage validation methodology: validating the dynamic aspect of each brake component and the brake assembly using modal testing data and the contact aspect using the experimental results of static contact pressure. A detailed 3-dimensional finite element model of an actual disc brake was developed. Brake pad surface topography is also taken into consideration. Good agreement is achieved between predicted and experimental results both in modal analysis and static contact pressure distributions. Once a validated model was obtained, contact analysis for dynamic condition of the disc brake is performed.